Correlation between parents anxiety level with parenting styles in autism spectrum children at Special-Educational-Needs (SEN) school students Bandung - Atmadiyanti, Ayu Lita; Sriati, Aat; Nurhidayah, Ikeu (University of Muhammadiyah Malang, 2018)
Autism spectrum children have a complex growth disorder that deals with communication, social interaction, and behavior which can cause anxiety disorder in parents. This anxiety can affect their parenting styles to children. The purpose of this study was to determine the correlationbetween parents anxiety level and parenting styles of children with autism spectrum disorder at Special-Educational-Need (SEN)(Indonesian : Sekolah Luar Biasa (SLB)) school students in Bandung. The method using correlational design. Samples were taken by using total samplingtechnique. This study used Zung Self-Rating Anxiety Scale. Data were analyzed by using Spearman Rank test. The result of the study found that 26 parents (54,2%) suffer moderate anxiety and 4 parents (8,3%) suffer severe anxiety, while parents implemented authoritative parenting is 26respondents (54,2%) and 9 parents (18,8%) implemented permissive parenting. There is a correlation between parents anxiety level and parenting styles in autism spectrum children at Special-Educational-Need (SEN) (Indonesian: Sekolah Luar Biasa (SLB)) school students in Bandung (p value = 0,009; r-value = 0,374). Based on result of this study, for the education institutions and health institutions espescially nurses are expected to educate parents about how to pressing anxiety level and implementing the right parenting styles in children with Autism Spectrum as well as the impact of the parenting